Enhancing the quality of life of people with intellectual disabilities from theory to practice - Kober, Ralph (Social indicators research series, 2011)
This book contains a series of articles written by international experts in the fields of intellectual disability and quality of life. These articles explore a broad range of issues that impact on the quality of life of people with intellectual disabilities and their families. The book commences with a general discussion on defining quality of life and family quality of life, and the appropriateness of using these constructs in the field of intellectual disability. This is followed by an analysis of the effects of living arrangements and employment on quality of life. The book concludes with discussions on the unique issues facing children with intellectual disabilities and their families, as well as the issues faced by people with intellectual disabilities living in developing countries. This book will be of interest to intellectual disability researchers, quality of life researchers, social scientists, social workers, professionals working with people with intellectual disabilities, and policy makers at all level of government. In fact, anyone with an interest in improving the quality of life of people with intellectual disabilities will benefit from this book.